Структурный и параметрический синтез системы стабилизации квазистатического технологического процесса - Куценко, Александр Сергеевич; Коваленко, Сергей Владимирович; Товажнянский, Владимир Игоревич (НТУ "ХПИ", 2015)
Предлагается один из возможных подходов к синтезу регулятора параметров технологического процесса, математическая модель которого представлена в виде системы трансцендентных уравнений, связывающих входы и выходы технологического процесса. Целью работы является адаптация методов современной теории управления к управлению квазистатическими процессами. Подробно рассмотрен линейный случай взаимосвязи "вход-выход" и квадратичный критерий качества процесса стабилизации параметров технологического процесса.

One of the possible approaches to the synthesis of regulator of the state of the technological process, which mathematical model is presented in the form of transcendental equations linking the inputs and outputs of the technological process is offered in the article. The objective of the research is the adaptation the methods of modern control theory to the quasi-static processes, given by the static mathematical models. The case of a linear relationship "input-output" and quadratic criterion of the quality of the process of state stabilization of the technological process is examined in detail. The advantages and disadvantages of quasi-static mathematical models of controlled processes are analyzed.
Structural and parametric synthesis of the stabilization system of the quasi-static technological process
Keywords: линейно-квадратичная задача; квазистатическая математическая модель; теория управления; linear-quadratic problem; quasi-static mathematical model; control theory